Determinant Analysis of Innovative Work Behavior of Hospitality Employees in Lake Toba Tourism Area through Employee Engagement: A Structural Equation Model Approach - Efendi, Efendi; Romi, Mochamad Vrans; Chandra, Erbin; Candra, Vivi; Sudirman, Acai (Valid: Jurnal Ilmiah, 2023)
The main objective of this research is to analyze the effect of transformational leadership and organizational climate on employee engagement and innovative work behavior. The research method in this study included library and field research designs with a quantitative approach. The research subjects taken in this study were employees who worked in hotels in the Lake Toba Tourism Area. The number of samples analyzed was 170 employees. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses the Smartpls statistical software. The results of the data analysis concluded that transformational leadership, organizational climate, and employee engagement positively and significantly influence innovative work behavior. The results of subsequent studies confirm that transformational leadership significantly affects employee engagement. The results of this study also suggest that organizational climate has no significant effect on employee engagement. Furthermore, the managerial implications of this research suggest that to increase employee engagement and innovative work behavior, companies can provide employees with opportunities to learn and develop. Employees who feel empowered and have opportunities to learn and develop are likelier to be engaged and innovative. Employees who feel empowered and have opportunities to learn and develop are likelier to be engaged and innovative.